Predictors of the Efficacy for Daytime Sleepiness in Patients With Obstructive Sleep Apnea With Continual Positive Airway Pressure Therapy: A Meta-Analysis of Randomized Controlled Trials - Li, Zhiqiang; Cai, Sijie; Wang, Jing; Chen, Rui (Frontiers in Neurology, 2022)
Abstract Objective: The main aim of this meta-analysis was to evaluate the predictors of the efficacy of continuous positive airway pressure (CPAP) in ameliorating excessive daytime sleepiness (EDS) in patients with obstructive sleep apnea (OSA). Methods: Randomized controlled trials (RCTs) published between January 1994 and October 2021 were searched in the PubMed, EMBASE, and Cochrane Library databases. The weighted mean differences (WMDs) for Epworth Sleepiness Scale (ESS) scores, the Multiple Sleep Latency Test (MSLT), and the Maintenance of Wakefulness Test (MWT) were pooled in STATA. Results: Forty-one RCTs involving 7332 patients were included. CPAP therapy was found to be significantly associated with changes in ESS (WMD=-2.14, P < 0.001), MSLT (WMD=1.23, P < 0.001) and MWT (WMD=1.6, P < 0.001). Meta-regression analysis and subgroup analysis indicated that in mild OSA, the efficacy of CPAP therapy for subjective EDS was limited to patients < 50 years of age, with a baseline BMI ≥ 30 kg/m2, baseline ESS score ≥ 11, therapy adherence for ≥ 3 h/night and treatment duration ≥ 2 months. In moderate OSA, significant differences were observed in the changes in ESS among groups stratified by baseline ESS score (p=0.005), adherence (p < 0.001), treatment duration (p=0.009), and trial design type (p=0.001). In severe OSA, this difference was observed among groups stratified by baseline BMI (p=0.028), baseline ESS score (p=0.001), and adherence (p=0.047). Patients with moderate-severe OSA, but not mild OSA showed significant improvements in MSLT. Patients with the age < 50 years or BMI ≥ 33 kg/m2 had more significant increase in MWT. Conclusions: CPAP therapy improved subjective and objective sleepiness in patients with OSA. Age, baseline BMI, baseline ESS score, adherence, and duration of treatment may predict the effects of CPAP on EDS in patients with OSA. Notably, the baseline ESS scores and adherence were stable predictors regardless of OSA severity.